If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(x-6)=9x+108
We move all terms to the left:
-9(x-6)-(9x+108)=0
We multiply parentheses
-9x-(9x+108)+54=0
We get rid of parentheses
-9x-9x-108+54=0
We add all the numbers together, and all the variables
-18x-54=0
We move all terms containing x to the left, all other terms to the right
-18x=54
x=54/-18
x=-3
| |x|-10=-5 | | `-3x+15=-96` | | -11=4(w-8)+3w | | (x)=x^2+6x+14 | | -21=y/9 | | x-120=-120 | | x+17/4=10 | | 4x6=98 | | a/11+14=11 | | 2x²-6x+9=0 | | -17=5x+8(x+6) | | y=35(1)+70 | | |-4x-2|+3=9 | | u/3-10=25 | | 0.75(y+1)=-6 | | k/5+10=13 | | −4x+7=9−2x | | 36=8(y-6)+4y | | w=16÷4 | | 180=4x+132 | | v^{2}=361 | | –4+7w=6w | | j+17=16 | | X=40,y= | | 5r-6=5(r-1) | | 3w+26=5(w+8) | | 60+9x=-2+10x | | 10q=–8+9q | | 5x+5=380 | | 5x+0.5=7x-0.05 | | 8x-30=192 | | 2y+6+5y=27 |